Learning Biostratigraphy in University of Gadjah Mada - Diyaning Ratri; Fitra Annurhutami (Berita Sedimentologi, 2014)
Biostratigraphy is an even-semester elective course (non-mandatory) only offered to sophomores and higher in Gadjah Mada University, Yogyakarta. Many students choose to take this course on their 4th semester since it will ease them to understand other advanced materials on the next semesters such as paleontology and stratigraphy analysis. The course usually starts in the 4nd week of February and held every Thursday for 2x50 minutes.